2019
DOI: 10.1093/dote/doz082
|View full text |Cite
|
Sign up to set email alerts
|

Baseline neutrophil–lymphocyte ratio holds no prognostic value for esophageal and junctional adenocarcinoma in patients treated with neoadjuvant chemotherapy

Abstract: SUMMARY Background: Several studies have reported that neutrophil–lymphocyte ratio (NLR) can predict survival in esophageal and gastroesophageal junction adenocarcinoma, as it reflects systemic inflammation. Hence, we aimed to determine whether baseline NLR holds prognostic value for esophageal adenocarcinoma patients treated with neoadjuvant chemotherapy (nCT) followed by surgery. Methods: We studied the data of 139 patients that received nCT before undergoing esophagectomy with curative intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Nevertheless, many other prognostic serum-based biomarkers have been assessed before NAC, but their prognostic value in this specific setting remains unclear. For example, the neutrophil-to-lymphocyte ratio (NLR) which has been largely assessed, did not predict complete response to NAC despite its good predictive value on oncological outcome in patients without NAC in other cancers such as breast, esophageal [32], or cervical cancer [33] [34,35]. It was only a potential predictor in association with other markers such as the platelet-to-lymphocyte ratio [35].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many other prognostic serum-based biomarkers have been assessed before NAC, but their prognostic value in this specific setting remains unclear. For example, the neutrophil-to-lymphocyte ratio (NLR) which has been largely assessed, did not predict complete response to NAC despite its good predictive value on oncological outcome in patients without NAC in other cancers such as breast, esophageal [32], or cervical cancer [33] [34,35]. It was only a potential predictor in association with other markers such as the platelet-to-lymphocyte ratio [35].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three articles were selected and included in our review. 1233 These studies were published between 2006 and 2020, properly reflecting the current clinical scenario. Ten studies (43.5%) were prospective, whereas 13 were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…All the main characteristics of the population enrolled in the selected studies are reported in Table 1. 1233…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations